Solar Water Splitting: Efficient Water Splitting Cascade Photoanodes with Ligand‐Engineered MnO Cocatalysts (Adv. Sci. 10/2018). Issue 10 (17th October 2018) - Lee, Mi Gyoung; Jin, Kyoungsuk; Kwon, Ki Chang; Sohn, Woonbae; Park, Hoonkee; Choi, Kyoung Soon; Go, Yoo Kyung; Seo, Hongmin; Hong, Jung Sug; Nam, Ki Tae; Jang, Ho Won
Abstract : The band edge positions of semiconductors determine functionality in solar water splitting. In article number1800727, Ki Tae Nam, Ho Won Jang, and co‐workers demonstrate cascade photoanodes with ligand engineered manganese oxide co‐catalyst nanoparticles to achieve enhanced photoelectrochemical performance. The proposed concept has considerable potential to explore a new efficient solar water splitting system.